MORPHOSTRUCTURAL CHARACTERISTICS AND BLOOD CONSTITUENTS OF DWARF RAM LAMBS FED MIXTURE OF ORANGE AND PINEAPPLE PULPS - M.I., Okoruwa; F.O., Bamigboye; M.K., Adewumi (European Scientific Journal, ESJ, 2014)
The study was conducted to assess the mixture of orange and pineapple pulps using morphostructural characteristics and blood constituents by ram lambs. Thirty growing ram lambs with mean weight of 8.00+0.52kg and aged between 9 and 10 months old were randomly allotted to three dietary treatments with ten ram lambs per treatment in a completely randomized design. The experimental diets which comprised A, B and C constituted mixture of orange and pineapple pulps in the following ratios respectively A = 30:40, B=35:35 and C=40:30. The results showed that treatment A was significantly (P<0.05) highest for bodyweight gain, height at wither, body length, fore and hind legs length, packed cell volume, haemoglobin, red blood cell, lymphocytes, monocytes, total protein. Albumin, calcium and phosphorus. Ear length, white blood cell, neutrophile, cholesterol and urea were significantly (P<0.05) better in treatment C. No significance (P>0.05) was observed for heart girth, tail length, eosinphils, basophils, globulin and creatinine. It can be concluded that mixture of orange and pineapple pulps in a ratio of 30:40 has a good potential to enhance body measurements and blood constituents of ram lambs.